Effect of Areca Nut Extract Tooth Paste on Tooth Discoloration - Shulhan Rijal; Aria Fransiska; Mustika Arini (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2025)
Background: Areca nut extract is an active compound that can be used as an alternative toothpaste ingredient because it has antibacterial properties that can prevent cavities, but the tannin and flavonoid content in areca nut extract has the potential to cause discoloration of tooth. Objective: To determine the effect of areca nut extract (Areca catechu L.) toothpaste on tooth enamel color. Materials and Methods: This study was a true experimental laboratory type using pre test - post test with control group design. The study sample was 28 post-extraction human premolars who met the inclusion and exclusion criteria. The samples were divided into 4 treatment groups, 7 samples each in the group brushed using areca nut extract toothpaste concentrations of 1,5%, 3%, 4,5% and toothpaste without areca nut extract. Samples were brushed 2 times a day for 14 days. Measurement of color change using ColorFlex EZ spectrophotometer. Results: The results of data analysis obtained the average value of color change for toothpaste concentration of 1,5% of 4,38, 3% concentration of 5,40, 4,5% concentration of 7,37 and without areca nut extract of 0,98. The results of the One Way ANOVA test obtained a p value <0,05, meaning that there were a significant effect in each treatment group. The results of Post Hoc LSD analysis showed significant differences between all treatment groups, except between the treatment groups using 1,5% concentration of areca nut extract toothpaste and 3% concentration of areca nut extract toothpaste. Conclusion: areca nut extract toothpaste has an effect on the color of tooth enamel. The 4,5% concentration of Areca nut extract toothpaste has a significant effect on tooth discoloration.